Total internal reflection microscopy studies on colloidal particle endocytosis by living cells - Byrne, Gerard (2009)
The purpose of this study was to develop novel optical microscopy techniques in order to investigate colloidal drug particle endocytosis by mammalian cells. A total internal reflection microscope (TIRM) was initially developed for high resolution cellular imaging. TIRM is a non-fluorescent imaging technique based on the principle of ‘scattering’ of the evanescent field created when a light beam undergoes total internal reflection at an interface between two media with different refractive indices, such as glass and air. The key design considerations with respect to development of a TIRM instrument are discussed. The technique is also compared and contrasted to the more commonly known non-fluorescent RICM (Reflection Interference Contrast Microscopy) technique using computer simulations. Time-lapse video TIRM is applied to imaging the interaction between A549 and 3T3 cells, and a polylysine coated substrate. Real-time label-free visualisation of 0.5 and 1 m polystyrene particle endocytosis by living cells is then demonstrated. Modifications to the TIRM system to include a dual-colour fluorescent TIRF (Total Internal Reflection Fluorescence) microscope are described in detail. Results are shown which demonstrate the ability of a combined TIRM/TIRF instrument to selectively image the basal cell membrane both label-free and fluorescently. 3T3 fibroblast cells were genetically modified using standard molecular biology protocols to express the fluorescent fusion protein EGFP-Clathrin LCa (enhanced green fluorescent protein clathrin light chain a). Finally, colloidal particle endocytosis by the genetically modified cell was imaged using the TIRM/TIRF microscope. Direct visualisation of the internalisation of 500 nm particles via clathrin coated pits in 3T3 cells was shown for the first time.